Public Interest in Merger Control: The Lay of the Land. (June 2020) - Mellott, Jenn; Ciric, Ruzica
In recent years, regulators and politicians have raised questions about whether merger control is "fit for purpose" in the modern economy, and in particular about whether the consumer welfare standard remains the appropriate lens through which to assess transactions, or whether merger control should consider the potential impact of a transaction on broader public interest (PI) objectives, such as employment, the environment, data privacy, national security, or industrial or trade policy. Many merger control regimes globally already include a public interest component, and in thinking about whether it would be reasonable or appropriate to add or strengthen the PI component of a merger control regime, it may be helpful to look at regimes that already include a PI component to consider the ways in which this may be structured and whether these standards are likely to be successful in achieving PI aims. This piece surveys the existing merger control regimes with a PI component to identify lessons that may be useful for jurisdictions considering whether and how to expand a merger control regime to include PI.